Mummies - Malam, John; Baker, Julian (Philadelphia, Pa. : Running Press Kids, 2003)
"Featuring clear pages that allow the reader to glimpse beneath the surface, See-through mummies will show you the secrets, legends, methods, and the exact step-by-step science of the practice of creating ancient mummies ..."
Includes index.
Keywords: Mummies -- Egypt; Antiquities; Egyption Civilization; Egypt; Egypt -- To 332 B.C.